The Implementation of Internet-Based Computer Network at SMP Negeri 21 Central Bengkulu - Hary Satria Pratama; Toibah Umi Kalsum; Hendri Alamsyah (Penerbit Jurnal Indonesia, 2021)
This study aims to design and build a computer network connection at SMP Negeri 21 Central Bengkulu. This study used an experimental research method. In this study, was carried out the performance of a proxy running on the system. From the results of the analysis, conclusions will be obtained regarding the benefits and more detailed functions of Mikrotik and SMB servers in the data or file sharing function. The results of this study show that the internet network has been running in accordance with what the writer hopes and can access the internet, clients from this server can also access the internet. As well as sending files using SMB server that has been determined by the writer. The SMB server can be used to send files that are placed on the Mikrotik router, so that the files can be accessed by connected to clients. Therefore in this study the writer only built LAN network using Mikrotik and sharing data with SMB Servers only.